2001
DOI: 10.1038/sj.leu.2402263
|View full text |Cite
|
Sign up to set email alerts
|

Marked bone marrow basophilia in a child with acute myeloid leukemia with a cryptic t(8;21)(q22;q22) chromosomal translocation

Abstract: Correspondence 1799 blot analysis. However, examples of pure ALL cells contains no or few if any, expression of the MPO gene, indicating that MPO could be the best marker of myeloid differentiation. In this case, no TCR and immunoglobulin-heavy and -light chain rearrangements were detected by Southern blot analysis. We thus report here a case of AML-M0 complicated with generalized granulocytic sarcoma, as confirmed by in situ hybridization (ISH) for the detection of MPO gene expression. AcknowledgementsWe wish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Cases with t(8;21) and basophilia have earlier been reported [25,26]. In one, the cytomorphological features were those of AML-M2 with basophilia [25], and in the second, additional chromosomal abnormality t(9;22) was present along with clinical and hematological features of CML [26]. On review, the first bone marrow of our patient had morphological features compatible with AML-M2 with increased basophils and eosinophils.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Cases with t(8;21) and basophilia have earlier been reported [25,26]. In one, the cytomorphological features were those of AML-M2 with basophilia [25], and in the second, additional chromosomal abnormality t(9;22) was present along with clinical and hematological features of CML [26]. On review, the first bone marrow of our patient had morphological features compatible with AML-M2 with increased basophils and eosinophils.…”
Section: Discussionsupporting
confidence: 51%
“…Cytogenetic studies in our case revealed t(8;21) (q22;q22), which is an unusual finding in acute basophilic leukemia. Cases with t(8;21) and basophilia have earlier been reported [25,26]. In one, the cytomorphological features were those of AML-M2 with basophilia [25], and in the second, additional chromosomal abnormality t(9;22) was present along with clinical and hematological features of CML [26].…”
Section: Discussionmentioning
confidence: 97%
“…[4][5][6][7] Previous reports including ours have demonstrated that t(8;21)AML shows high levels of CD34 and DR expression, with a prevalent positivity for CD19 and CD56 surface markers and a low expression of CD33 and CD7 when compared to AML with normal or other aberrant karyotypes, and eosinophilia is also often observed in t(8;21) AML. [8][9][10][11][12][13][14][15] Cytogenetically, the t(8;21) AML is frequently associated with a loss of the sex chromosome Y in males and inactive X in females; 3 3.4% of the cases are variant translocations. 16 However, the influence of these variant translocations or additional chromosomal abnormalities on the characteristics of t(8;21) AML is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings suggest that IKAROS alterations are associated with disease acceleration and basophil expansion in CML . Basophilic differentiation may occur in AML carrying t(8;21)(q22;q22)/ RUNX1 ‐ RUNX1T1 ; however, reactive BM basophilia in response to a factor produced by leukemia blasts was suggested in one case . t(6;9)(p22;q34)/ DEK ‐ NUP214 is observed in AML with or without monocytic features and 44–62% of cases show >2% basophilia in PB and BM .…”
Section: Discussionmentioning
confidence: 99%